2014
DOI: 10.3109/14767058.2014.980807
|View full text |Cite
|
Sign up to set email alerts
|

Fetal growth restriction: risk factors for unplanned primary cesarean delivery

Abstract: The rate of vaginal delivery is high in cases of FGR undergoing a trial of labor. We recommend that these patients undergo a trial of labor. Patients with oligohydramnios and those requiring prostaglandins for cervical ripening should be counseled regarding a significantly higher risk of cesarean delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Induction of labor has been shown to be associated with an increased risk of Cesarean delivery; however, both mathematical modeling and a multicenter randomized trial demonstrated that this is not the case in low‐risk term pregnancies. Nevertheless, among SGA fetuses, there remains a concern for the safety of prostaglandin use for labor induction in pregnancies with fetal growth restriction (FGR).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of labor has been shown to be associated with an increased risk of Cesarean delivery; however, both mathematical modeling and a multicenter randomized trial demonstrated that this is not the case in low‐risk term pregnancies. Nevertheless, among SGA fetuses, there remains a concern for the safety of prostaglandin use for labor induction in pregnancies with fetal growth restriction (FGR).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified certain antenatal and intrapartum risk factors that increase the risk of operative delivery [5][6][7][8][9][10][11][12] . These include abnormal umbilical artery (UA) Doppler studies, low cerebroplacental ratio, oligohydramnios, prostaglandin use and non-reassuring fetal heart tracing (NRFHT).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies identified the main obstetric pathologies (e.g. fetal growth restriction, preeclampsia) as risk factor for primary non-elective CS and invited to consider the maternal characteristics and different assistential levels as potential bias [20,21]. Moreover, the analysis of the indicators in the first two classes of Robson, known to include the women with the lowest risk of CS, showed that fetal distress, malpresentation, and failed induction were the most frequent one.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that because the delivery of newborns with FGR is associated with NRFS, the rate of cesarean delivery is high (14-40.9%) [18][19][20][21][22][23], particularly in cases with low CPR [23]. The indication for cesarean delivery was fetal distress in 9.5-29% of these cases [18][19][20]. In our study, because women who experienced cesarean delivery before the active phase of labor were excluded, the cesarean delivery rate was only 4% (5/127).…”
Section: Discussionmentioning
confidence: 99%
“…We performed a power analysis, which estimated that 152 women were needed to detect a difference in the cesarean delivery rate of 15% between groups to achieve 80% power and an α-value of 0.05. Based on previous studies, a 15% difference between groups was selected [11,18]. A statistical analysis was performed using JMP® 13 (SAS Institute Inc., Cary, NC, USA).…”
Section: Methodsmentioning
confidence: 99%